Motivation Concept in Buddhism - ทวีสุข กนกรัตน์สิริ; แก้วชัง พญ.กรองกาญจน์ (Journal of Educational Review Faculty of Education in MCU, 2018)
There are 2 types of motivation in Buddhism: positive motivation consisting Chanda or the will to do that should be encouraged to happen and negative motivation consisting of 3 Cravings: 1) Craving for sensual pleasure, 2) Craving for existence, and 3) Craving for non-existence, that should be reduced and eradicated. On the other hand, craving can be used as a powerful motivation to push our mind for the higher achievement, but it must be applied with the wholesome principles; the Noble Eightfold Path, Patisambhida, Dasabalañana and Kalyanamitta.